Influence on The Speed of Processing Multiple Implementation Models Wetland - Anwar Manik; Achwil Putra Munir; Saipul Bahri Daulay (Jurnal Rekayasa Pangan dan Pertanian, 2014)
.Analysis of these wetland cultivating was aimed to obtain information on wetland cultivating until ready for planting using a two-wheeltractor, calculating the effective field capacity, field efficiency, and fuel consumption for cultivation until the condition of the land ready for planting with working speed variations. This study uses a factorial randomized block design with two factors.The first factor was the treatment variation until ready for planting and the second factor was the variation of speed (1m/s, 1,2m/s, and 1,4m/s). Parameters measured were land cultivating capacity, fuel consumption, efficiency of tractors, and economic analysis. Results of this study showed that the difference in treatment until ready for planting had a significant effect on effective field capacity, efficiency, and fuel consumption. The highest Effective Field Capacity (EFC) of any cultivating until the rice fields ready for planting was at a speed of 1.4m/s. The highest processing efficiency was obtained at a speed of 1.4m/s. The greatest fuel consumption obtained in the second cultivation pattern. Keywords: tractors, paddy fields,cultivatinguntilready to plant.